(3GdKbI (B:s (3GdaVGFd GdELJeGYjI hOhQgG aj Ndb GdQNGA GdEbJUGOj (B/s - (3ahchjGeG, aQGfSjSs ((3OeTb(B: s (3efJOi GdYdGbGJ GdYQHjI hGdOhdjI(B, s, 2002)
(3acQI GdKbI, eLJeYGJ GdKbI GdeJOjfI hGdeaGQbI aj Gdbje GdYGFdjI ,eLJeYGJ GdKbI GdYGdjI hJMOjGJ GdMaGX Ydi GdJhGUd GdELJeGYj , GdeLJeY GdCeQjcj hCReI GdKbIs
Keywords: (3GdKbIs